IMPLEMENTASI APLIKASI PEMESANAN MAKANAN SERVICE DAN RESERVASI BERBASIS WEB PADA RESTORAN EKA RIA - Elis Sondang Dasawati, S.Kom., MM., M.Kom (Institut Bisnis dan Informatika Kwik Kian Gie, 2017)
Increasingly Evolving her a restaurant, the greater the data that must be processed to be accurate information manual processing has many problems few examples of cases when an employee or any admin convey information about the order list. menu prices were not reasonable because it is too expensive if it happens then the restaurants need to spend money to print the list menu again and be a waste of capital. Seeing an issue with such problems researchers offered a WEB-based application implementation to process the booking, price information, promotions, reservations and sales reports. This application is made with programming language PHP Hypertext Prepocessor